Desnudação geoquímica na evolução da Serra do Espinhaço Meridional - MG - Brasil - Leonardo Cristian Rocha (2011)
This study aims to understand how geochemical processes in the development of the landforms of the Serra do Espinhaço Meridional (SdEM) and contribute to the understanding of the spatial distribution of loss rates by chemical erosion. To this were done, digital terrain models (DTM), preparation of a geological map containing the main rock types and structures of SdEM, chemical analyzes of rock, soil and water. In addition to the statistical treatment of geochemical data to recognize the main components and their associations, as well as the spatial distribution of the same SdEM. The weathering of quartzite in the study area consists of quartz dissolution by the arrangement of crystals. So quartzite loses cohesion and reduces the sand. In sub-surface weathering occurs preferentially in the planes of stratification. The geochemical emptying can then break down the quartzite. This fact, coupled with the sub-surface weathering, promotes the lowering of the landforms, forming flattened surfaces in the Espinhaço Meridional. The leaching of silica alteration mantles occurs in advanced stages of weathering, providing the formation of oxides and hydroxides of iron and aluminum, when in sufficient quantities, can lead to processes in lateritization SdEM. The lateritization intense leaching and favored the formation of goethite, hematite and gibbsite, those elements that suggest the area is long on the influence of a hot and humid climate. These same elements favor the translocation of organic matter in soils where the source material is poor in clay (psammitic rocks) favoring the formation of Spodosols. The combination of geochemical processes leads to a generalized loss of a large part of all elements found, except those of low mobility such as titanium and zirconium. In the mass it became clear, the data suggest the loss of 41% of the aluminum in some profiles analyzed. These facts suggest that the Espinhaço Meridional presents a significant drain geochemical today, meaning a progressive loss of volume, expressed more intensely in the mantle of weathering.